(untitled) (Педагогіка вищої та середньої школи, 2004)
Personality, possibilities of its development, its freedom and inequity are the subject of spiritual, intellectual, moral and esthetic search of home philosophers educationalist and psychologists. The article is devoted to the study of laws of personality development, to its perfectioning taking into account the conceptual philosophical approach to the problem.